The Role of PDGFs and PDGFRs in Colorectal Cancer - Roberta M. Manzat Saplacan; Loredana Balacescu; Claudia Gherman; Romeo I. Chira; Anca Craiu; Petru A. Mircea; Cosmin Lisencu; Ovidiu Balacescu (Mediators of Inflammation)
Introduction. Colorectal cancer (CRC) is an important cause of morbidity and mortality worldwide. Angiogenesis was reported as one important mechanism activated in colorectal carcinogenesis. Tumor microenvironment associated angiogenesis involves a large spectrum of signaling molecules and deciphering their role in colorectal carcinogenesis still represents a major challenge. The aim of our study is to point out the diagnosis and prediction role of PDGF family and their receptors in colorectal carcinogenesis. Material and Methods. A systematic search in Medline and PubMed for studies reporting the role of platelet-derived growth factors (PDGFs) and their receptors (PDGFRs) in tumor biology related to CRC was made. Results. PDGFs are important growth factors for normal tissue growth and division, with an important role in blood vessel formation. PDGFs/PDGFRs signaling pathway has been demonstrated to be involved in angiogenesis mainly by targeting pericytes and vascular smooth muscle cells. High levels of PDGF-BB were reported in CRC patients compared to those with adenomas, while elevated levels of PDGFR α/β in the stroma of CRC patients were correlated with invasion and metastasis. Moreover, PDGF-AB and PDGF-C were correlated with early diagnosis, cancer grading, and metastatic disease. Conclusions. Both PDGFs and PDGFRs families play an important role in colorectal carcinogenesis and could be considered to be investigated as useful biomarkers both for diagnosis and treatment of CRC.